2016
DOI: 10.1088/1367-2630/18/7/073015
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Bose–Einstein condensation in contact with a thermal reservoir

Abstract: We investigate the real-time dynamics of open quantum spin-1/2 or hardcore boson systems on a spatial lattice, which are governed by a Markovian quantum master equation. We derive general conditions under which the hierarchy of correlation functions closes such that their time evolution can be computed semi-analytically. Expanding our previous work (2016 Phys. Rev. A 93 021602) we demonstrate the universality of a purely dissipative quantum Markov process that drives the system of spin-1/2 particles into a tot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…This allows one to obtain exact results on the dynamics of correlation functions [18][19][20][21][22][23] as well as entanglement-related quantities [24,25]. Furthermore, it has also been realized that in some models, not necessarily integrable, local correlation functions satisfy closed hierarchies of equations of motion, provided that the Lindbladian satisfies certain conditions [26][27][28][29][30][31][32] (although in these cases the full spectrum typically remains out of reach). Very recently, further progress has been made in this direction, with the discovery of Lindbladians that can be mapped onto known Yang-Baxter interacting integrable models [33][34][35][36][37][38][39][40][41][42].…”
mentioning
confidence: 99%
“…This allows one to obtain exact results on the dynamics of correlation functions [18][19][20][21][22][23] as well as entanglement-related quantities [24,25]. Furthermore, it has also been realized that in some models, not necessarily integrable, local correlation functions satisfy closed hierarchies of equations of motion, provided that the Lindbladian satisfies certain conditions [26][27][28][29][30][31][32] (although in these cases the full spectrum typically remains out of reach). Very recently, further progress has been made in this direction, with the discovery of Lindbladians that can be mapped onto known Yang-Baxter interacting integrable models [33][34][35][36][37][38][39][40][41][42].…”
mentioning
confidence: 99%
“…We emphasize, however, that the low-lying Fourier modes have a sizable amplitude at late times which again indicates that no global phase coherence is established. We note that this is in contract to dissipative Bose-Einstein condensation of hardcore bosons for which all low-lying Fourier modes decay at late times [24,25]. In fact, the asymptotic value G ∞ 0 strongly depends on the lattice size N as shown in Fig.…”
Section: A Truncated Wigner Approximation (Twa)mentioning
confidence: 90%
“…For instance, the hierarchy of time evolution equations of correlation functions closes for a purely dissipative process that drives a system of hardcore bosons into a Bose-Einstein condensate. In this specific case, it was shown that the dissipative gap that determines the long-time behavior of the quantum manybody system shows an intriguing finite-size scaling as a function of dimensionality which results in a increase of efficiency in higher dimensions [24,25]. It is, however, unclear whether this strong dependence of the time scales on dimensionality is a generic feature of tailored dissipative processes or rather a special property of the considered state preparation protocol.…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic feature of these models is the fundamental boson or fermion operators in these models fulfil linear equations of motion and concomitantly so do the Green's functions of interest. Another step towards obtaining exact solutions of many particle Lindblad equations was the discovery that there exist classes of models in which some or all local correlation functions satisfy closed hierarchies of equations of motion [24,25,26,27,28,29,30]. This permits one to obtain some exact results on the dynamics although full solutions typically remain out of reach.…”
Section: Introductionmentioning
confidence: 99%